Pharmacokinetic and Pharmacodynamic Properties of Metronidazole in Pediatric Patients With Acute Appendicitis: A Prospective Study. (16th May 2018) - Child, Jason; Chen, Xinhui; Mistry, Rakesh D; Somme, Stig; MacBrayne, Christine; Anderson, Peter L; Jones, Ronald N; Parker, Sarah K
Abstract: Background: Metronidazole is traditionally dosed every 6–8 hours even though in adults it has a long half-life, concentration-dependent killing, and 3-hour postantibiotic effect. Based on this logic, some pediatric hospitals adopted once-daily dosing for appendicitis, despite limited pharmacokinetics-pharmacodynamics (PK/PD) in children. We studied pediatric patients with appendicitis given metronidazole once daily to determine whether this dosing would meet target area under the curve (AUC)/minimum inhibitory concentration (MIC) ratio of ≥70 for Bacteroides fragilis . Methods: One hundred pediatric patients aged 4–17 years had an average of 3 blood draws per patient during the first 24 hours after a 30 mg/kg per dose of intravenous metronidazole. Concentrations of drug were determined using validated liquid chromatography and tandem mass spectrometry. A NONMEM model was constructed for determining PK, followed by Monte Carlo simulations to generate a population of plasma concentration-time AUC of metronidazole and hydroxy-metronidazole. Results: Simulated AUC values met target attainment (AUC/MIC ratio of ≥70 to B fragilis MICs) for 96%–100% of all patients for an MIC of 2 mcg/mL. For MICs of 4 and 8 mcg/mL, target attainment ranged from 61% to 97% and 9% to 71%, respectively. Areas under the curve were similar to that of adults receiving 1000 mg and 1500 mg q24, or 500 mg q8 hours. Conclusions: Metronidazole, 30 mg/kg per dose, once daily achieved AUC target attainment for B fragilis with an MIC of 2 mcg/mL or less in pediatric appendicitis patients. Based on this and studies in adults, there does not seem to be any PK/PD advantage of more frequent dosing in this population.